2-(y-5)(7-2y)-y(2y-3)=

Simple and best practice solution for 2-(y-5)(7-2y)-y(2y-3)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2-(y-5)(7-2y)-y(2y-3)= equation:


Simplifying
2 + -1(y + -5)(7 + -2y) + -1y(2y + -3) = 0

Reorder the terms:
2 + -1(-5 + y)(7 + -2y) + -1y(2y + -3) = 0

Multiply (-5 + y) * (7 + -2y)
2 + -1(-5(7 + -2y) + y(7 + -2y)) + -1y(2y + -3) = 0
2 + -1((7 * -5 + -2y * -5) + y(7 + -2y)) + -1y(2y + -3) = 0
2 + -1((-35 + 10y) + y(7 + -2y)) + -1y(2y + -3) = 0
2 + -1(-35 + 10y + (7 * y + -2y * y)) + -1y(2y + -3) = 0
2 + -1(-35 + 10y + (7y + -2y2)) + -1y(2y + -3) = 0

Combine like terms: 10y + 7y = 17y
2 + -1(-35 + 17y + -2y2) + -1y(2y + -3) = 0
2 + (-35 * -1 + 17y * -1 + -2y2 * -1) + -1y(2y + -3) = 0
2 + (35 + -17y + 2y2) + -1y(2y + -3) = 0

Reorder the terms:
2 + 35 + -17y + 2y2 + -1y(-3 + 2y) = 0
2 + 35 + -17y + 2y2 + (-3 * -1y + 2y * -1y) = 0
2 + 35 + -17y + 2y2 + (3y + -2y2) = 0

Reorder the terms:
2 + 35 + -17y + 3y + 2y2 + -2y2 = 0

Combine like terms: 2 + 35 = 37
37 + -17y + 3y + 2y2 + -2y2 = 0

Combine like terms: -17y + 3y = -14y
37 + -14y + 2y2 + -2y2 = 0

Combine like terms: 2y2 + -2y2 = 0
37 + -14y + 0 = 0
37 + -14y = 0

Solving
37 + -14y = 0

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '-37' to each side of the equation.
37 + -37 + -14y = 0 + -37

Combine like terms: 37 + -37 = 0
0 + -14y = 0 + -37
-14y = 0 + -37

Combine like terms: 0 + -37 = -37
-14y = -37

Divide each side by '-14'.
y = 2.642857143

Simplifying
y = 2.642857143

See similar equations:

| -2(8w-1)+4w=6(w+2) | | 4u+3-5(-2u-1)=6(u-1) | | 2x-5*2=10 | | 2y+(5-7y)-9-(3y-2)= | | f(x)=x^3-2.25x^2-3x | | x+2*4=4 | | 427xX=X | | x+0y=4 | | Y+3z=10 | | x-6=-31 | | x(x+3)(x+3)=x(x-3)(x+3) | | 6-4(x+5)=-16 | | K=9r-a | | 2x^2+y^2=17 | | -4(y+5)=8-6(y+7) | | 7y-(8y+9)=10 | | 2x^4+20x^2+18=0 | | 5x=3x-4x+10+2 | | -4(-2)(-5)= | | 4+5=445 | | [(x^3+4X)(6X+2)]+[(3X^2+2X-5)(3X^2+4)]= | | 4+4=445 | | X=(x+500)+4x-1100 | | 2ln(2x)=4-ln(25) | | H=-16x^2+108x+160 | | X=-16x^2+108x+160 | | 5a+4c=7549.47 | | X=2x^2-1600 | | 4x+3=5-2x | | 5a+4c=100 | | 6.1x-3.5=20.9 | | X+3x+5=117 |

Equations solver categories